1998
DOI: 10.1097/00006842-199811000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Signs, Symptoms, and Ill-Defined Conditions in Persian Gulf War Veterans

Abstract: Ill-defined conditions identified by physicians in Gulf War veterans are most often symptoms. More definitive, often psychological, diagnoses can be made by increasing the intensity of the evaluation and by multidisciplinary input. Evidence for a new or unique illness related to wartime exposures did not emerge from this analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…[39] Ancient Chinese medicine theory encourages women taking Chinese herbal medicine to build up their blood supply in order to reserve strength for each menstruation cycle because women expect a significant amount of blood to be lost during that. [4041] The anemia-related fatigue, dizziness, and palpitations might be the major reasons that lead to the patient's behavior of seeking TCM and receiving prescriptions of conventional drugs and CHPs concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…[39] Ancient Chinese medicine theory encourages women taking Chinese herbal medicine to build up their blood supply in order to reserve strength for each menstruation cycle because women expect a significant amount of blood to be lost during that. [4041] The anemia-related fatigue, dizziness, and palpitations might be the major reasons that lead to the patient's behavior of seeking TCM and receiving prescriptions of conventional drugs and CHPs concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…Nightmare frequency as determined as the mean number of nightmares recalled upon awakening each morning per week, which was logged in the sleep diary. Because trauma-exposed individuals with chronic nightmares reported a broad range of dysphoric dreams (25), participants were asked to log all distressing dreams (nightmares) they experienced. This broader definition of nightmares was intended to provide a more ecologically valid assessment of the effects of prazosin or BSI on distressing dreams in military veterans with PTSD symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with previous studies that have shown that sleep disturbances are highly prevalent and strongly correlated with PTSD in combat deployment military veterans. [42][43][44][45][46][47][48][49][50][51] Although sleep difficulties often follow TBI or blast exposure, 52 the present study suggests that prior blast exposure or TBI alone, in the absence of current chronic concussive symptoms, does not adversely affect sleep quality, insomnia, disruptive sleep disturbances, or objective sleep measures beyond the effects of PTSD. Indeed, post hoc analyses revealed that service members and veterans with PTSD endorsed higher scores on the ISI, PSQI, and PSQIA than those without PTSD diagnosis, regardless of presence or absence of blast exposure.…”
Section: Discussionmentioning
confidence: 89%